Conceptualising Quality in Spatial Planning - Gernot Stöglehner (Raumforschung und Raumordnung, 2019)
Quality discourses help to legitimate professions. This article therefore addresses the crucial question of how quality can be framed in spatial planning. Based on the context of spatial planning in Austria, this article introduces a normative framework for quality in spatial planning that considers the four dimensions of content, planning methodology, planning process and legal compliance, and shows howthese four dimensions are interlinked. Furthermore, it discusses how quality can be enhanced by concerted governmental action and further education for planners. It is argued that planners might need to adopt a new role as 'teachers' in planning processes to facilitate societal learning processes in order to raise the quality of planning. Finally, it is concluded that the quality debate in spatial planning can be useful to calibrate expectations of planners and society to directly influence sustainable spatial development through spatial planning, to communicate achievements in planning, to raise awareness for sustainable spatial development, and to improve legal frameworks, planning methodology, and planners' training and further education.